Quiet crisis in India : economic development and American policy - Lewis, John Prior (Washington, D.C. : The Brookings Institution, 1962)
This is an analysis of India's economic development program and the impact of this program upon the foreign aid policy of the United States prior to 1962 and the intensification of the Sino-Indian border conflict. The book first examines the basic strategy of India's development plans and then the issues and techniques of American aid.
Reprint of the ed. published by Brookings Institution, Washington.
Includes bibliographical references and index.
lje 03/10/2018
Loans
Keywords: Economic assistance, American; Economic development; India